Journey to the Promised Land - Peters, Nonja (2000)
This exhibition was prepared for the Northam Multicultural Festival and initially on display in a marquee for the day with shipping lists of ships that plied the Europe Fremantle journay. It was later put on display in the Railway Museum Northam where it still resides. It was also on display in the Dutch Club Perth for special events.